THE WORK OF WASHINGTON IRVING AND THE SKILL OF CREATING MYSTICAL MOTIFS AND CHARACTERS IN UZBEK PROSE - Haqberdiyeva Husnubonu; Bozorov Orif Chamanovich (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article delves into the intricate relationship between the creative legacy of Washington Irving and the emergence of mystical (irfoni) motifs and character development techniques within modern Uzbek prose. By examining key works of both Irving and prominent Uzbek writers, the study identifies potential influences and parallels in narrative structure, thematic exploration, and the portrayal of nuanced characters. Furthermore, it analyzes how indigenous Uzbek cultural and philosophical traditions have shaped the adaptation and indigenization of these literary elements. The research employs a comparative literary analysis methodology, drawing upon textual evidence and critical interpretations to illuminate the cross-cultural literary dialogue.